posted by Alexandria on .
I'm not sure if anyone saw my question yesterday, but here it is again. Even if you can only answer 1 or 2 of the questions, that is fine. I am so confused with the rules of exponents. I know them, but I have a hard time applying them because of all the steps. I was wondering if someone would be willing to answer these questions, because I am unsure if my answers are right.
x to the third power y to the negative two power/x to the negative two power times y to the fourth power=
2x to the neg. second power (3x to the fourth - 6x to the econd)=
(-2x to the third)(-3x to the neg second) both expressions to the neg second
(2x to the second y to the negative second) to the third power
(2x to the negative fifth y to the fourth) to the third
Thank you your help is genuinely appreciated.
x^3 y^-2 / [ x^-2 y^4]
3 - -2 = 5
-2 -4 = -6
2 x^-2 ( 3 x^4 - 6 x^2 )
-2+4 = 2
-2 +2 = 0 remember anything^0 = 1
6 x^2 -12 x^0 = 6 x^2 -12